Enhancing Animal Husbandry Skills of Inmates at the Class IIB Sleman Penitentiary through the "Ayam Bahagia" Program - Dio Fico Felsidan Diatmono; Anisya Ratna Komalasari; Shita Al-addawiyah Lampart; Briantoro Imam Sudrajat; Chusnul Hanim (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Former inmates who experience discrimination while seeking employment may be more likely to recidivism if they do not have or lack the necessary skills. This issue is also faced by former inmates from the Sleman Class IIB Penitentiary, Yogyakarta Special Region, so several coaching in self-reliance and skills, e.g., animal husbandry, were provided in "Kampung Asimilasi" for inmates. However, there are problems with the animal husbandry of laying hens due to the lack of knowledge about proper management practices among correctional officers as facilitators. To address this, the "Ayam Bahagia" program was developed to provide correctional officers and inmates with the knowledge and practical skills they need to effectively and properly manage the raising of laying hens. The program covered the preparation, implementation, monitoring, and evaluation through a blended delivery: offline and online methods. Six correctional officers and eight inmates followed this program. A pre-test and post-test measured the increase in knowledge and practical skills. Data were analyzed using t-test. This program has resulted in a significant increase (P>0.005) in knowledge and skills related to animal husbandry. Correctional officers have been able to become facilitators for inmates with adequate ability, and inmates have been able to raise laying hens independently.